2019
DOI: 10.1002/mrm.27854
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the 12‐lead ECG using a novel MR‐compatible ECG sensor network

Abstract: Purpose: Current electrocardiography (ECG) devices in MRI use non-conventional electrode placement, have a narrow bandwidth, and suffer from signal distortions including magnetohydrodynamic (MHD) effects and gradient-induced artifacts. In this work a system is proposed to obtain a high-quality 12-lead ECG. Methods: A network of N electrically independent MR-compatible ECG sensors was developed (N = 4 in this study). Each sensor uses a safe technology -short cables, preamplification/digitization close to the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…This can be explained by the specificities of the Schiller dataset. The Schiller dataset is composed of reconstructed 12-lead ECGs, which reduced MHD amplitudes by design [44]. As a result, training without GAN data augmentation, as well as the PT algorithm, performed well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the specificities of the Schiller dataset. The Schiller dataset is composed of reconstructed 12-lead ECGs, which reduced MHD amplitudes by design [44]. As a result, training without GAN data augmentation, as well as the PT algorithm, performed well.…”
Section: Discussionmentioning
confidence: 99%
“…This is a reconstructed dataset containing 12-lead MHD-distorted ECGs [44] from 3 subjects in HF acquired in an idle 3T MRI scanner (Magnetom Prisma, Siemens, Erlangen, Germany) using a prototype sensor (Schiller AG, Baar, Switzerland) at 1000 Hz. A total of 69 R-peaks were manually annotated by an ECG expert, for a total duration of 62 s.…”
Section: Schillermentioning
confidence: 99%
“…The results showed that 80.2% of the reconstructed ECGs were similar to the reference 12-lead ECG, with no differences noticed from observers. Dos Reis et al proposed a device that reconstruct the 12-lead ECG using a MR-compatible ECG sensor network [16]. The study showed that the 12-lead ECG can be reconstructed with 4 MR-compatible sensors inside MR with the mean correlation coefficient of 0.887.…”
Section: Introductionmentioning
confidence: 99%